2009
DOI: 10.1007/s12594-009-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of late archaean granitoids in the northern part of Eastern Dharwar Craton, Southern India: Implications for transitional geodynamic setting

Abstract: Abstract:The results of field, petrographic and geochemical work of the granitoids of Hutti-Gurgunta area in the northern part of Eastern Dharwar Craton (EDC) is presented in this paper. This crustal section comprises polyphase banded to foliated TTG gneisses, middle amphibolite facies Gurgunta schist belt and upper greenschist facies Hutti schist belt and abundant granite plutons. The focus of the present study is mainly on basement TTG gneisses and a granite pluton (~ 240 sq km areal extent), to discuss crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 61 publications
(87 reference statements)
0
5
0
3
Order By: Relevance
“…Models put forward range between uniformitarian plate tectonic amalgamation by subduction in the Neoarchean (Chadwick et al, , 2007Moyen et al, 2001;Ram Mohan et al, 2013) and other models supporting formation by mantle plumes (Jayananda et al, 2000), sagduction (Choukroune et al, 1995;Chardon et al, 1998) or a combination of subduction and plume-related processes (Naqvi et al, 2002(Naqvi et al, , 2006Manikyamba and Kerrich, 2012). Geochemical evidence for a convergent margin setting for the Dharwar craton is becoming increasingly favored in the literature: felsic volcanics and granitoids in the northern EDC greenstone belts have adakitic characteristics including Sr/Y (>40) and La/Yb (>20) ratios indicative of slab melting (Naqvi et al, 2006(Naqvi et al, , 2008Prabhakar et al, 2009). Boninites are found in the Archean Gadwal greenstone belt of EDC (Manikyamba et al, 2005) and negative HFSE anomalies in the Mesoproterozoic Siddanpalli kimberlites have been interpreted to imply a subducted component in their mantle Fig.…”
Section: Implications For the Geodynamic Evolution Of The Dharwar Cratonmentioning
confidence: 98%
“…Models put forward range between uniformitarian plate tectonic amalgamation by subduction in the Neoarchean (Chadwick et al, , 2007Moyen et al, 2001;Ram Mohan et al, 2013) and other models supporting formation by mantle plumes (Jayananda et al, 2000), sagduction (Choukroune et al, 1995;Chardon et al, 1998) or a combination of subduction and plume-related processes (Naqvi et al, 2002(Naqvi et al, , 2006Manikyamba and Kerrich, 2012). Geochemical evidence for a convergent margin setting for the Dharwar craton is becoming increasingly favored in the literature: felsic volcanics and granitoids in the northern EDC greenstone belts have adakitic characteristics including Sr/Y (>40) and La/Yb (>20) ratios indicative of slab melting (Naqvi et al, 2006(Naqvi et al, , 2008Prabhakar et al, 2009). Boninites are found in the Archean Gadwal greenstone belt of EDC (Manikyamba et al, 2005) and negative HFSE anomalies in the Mesoproterozoic Siddanpalli kimberlites have been interpreted to imply a subducted component in their mantle Fig.…”
Section: Implications For the Geodynamic Evolution Of The Dharwar Cratonmentioning
confidence: 98%
“…Based on these grounds, and crystallization/differentiation trend as visualised through various petrochemical diagrams, it can be concluded that the abundant quartz diabases were available in greater bulk after the differentiation of the parent tholeiite magma and the depth of parent magma formation was probably greater and the silica saturated fractionates were derived at a depth lesser than 60 km, since silica saturated tholeiite cannot exist below that depth [31]. Subsequently, they intruded as mafic sweats into the granitoid rocks which in turn formed in a subducting geodynamic setting [34].…”
Section: Petrogenesismentioning
confidence: 98%
“…Over the past few decades, rocks with strong geochemical similarities to the leucogranodioritegranite suite have been described from the central Pilbara and Yilgarn cratons (Transitional TTG;Champion & Smithies 2001, 2003, Wyoming province (GG suite of Frost et al 2006), Tanzania craton (Neoarchean granitoids; Opiyo-Akech et al 1999), Dharwar craton (Arsikere-Banavara and Chitradurga-Jampalnaikankote-Hosdurga suites, Jayananda et al 2006, and granitoids of the Hutti-Gurgunta area, Prabhakar et al 2009), and Karelia terrane (Transitional TTG; Mikkola et al 2011). These works have contributed to identifying this new group of Archean granitoids and to estimating the true volume of each plutonic component in the gray gneiss complexes (Moyen & Martin 2012).…”
Section: Petrogenesismentioning
confidence: 99%